Experimental and theoretical investigations of Cs+ adsorption on crown ethers modified magnetic adsorbent - Liu, Zhong; Zhou, Yongquan; Guo, Min; Lv, Baoliang; Wu, Zhijian; Zhou, Wuzong (Journal of hazardous materials, 2019)
[Display omitted] •A bifunctional absorbent for Cs+: Fe3O4@18-Crown-6 ether is developed.•The adsorbent has a superparamagnetic property, allowing an easy recycling.•The adsorbent has a high capacity and high selectivity of Cs+ adsorption.•The experimental results are supported by the DFT calculations. Carboxyl Fe3O4 nanoparticles (Fe3O4@R−COOH) modified with 18-Crown-6 ether functional groups have been prepared via an amidation reaction and used as bifunctional adsorbent for Cs+. The adsorbent has a superparamagnetic property, allowing an easy recycling, and a high capacity of Cs+ adsorption on the crown ether. The adsorption isotherms and kinetic behaviors agree well with the Langmuir and the pseudo-second-order models. The material exhibits a high selectivity for Cs+ in the solution with co-existing cations (NH4+, Rb+, K+, Na+ and Li+). A theoretical calculation according to density functional theory (DFT) is used to estimate the structure of Cs+ adsorption on crown ether, demonstrating an exothermic process and showing a good agreement with the experimental observations. The adsorption behavior is affected not only by the size of macrocyclic crown ethers, but also by the chelating symmetry and the binding energy. The newly developed adsorbent has a potential application for removing cesium out of wastewater and salt lakes.